Human-wildlife conflicts in Mexico: Review of status and perspectives - Flores-Armillas, Victor Hugo; Valenzuela-Galván, David; Peña-Mondragón, Juan L.; López-Medellín, Xavier (Ecosistemas y Recursos Agropecuarios, 2019)
Human wildlife conflicts (HWC) represent a global challenge for the conservation of species. We registered all the available scientific publications on this subject from 1983 to 2017, in order to analyze the HWC research performed in Mexico. Our results indicate that this subject has been scarcely studied, with less than half of the studies published in scientific journals. The reviewed documents focus on the description and quantification of damage by wildlife, with a total of 112 species mentioned including birds, amphibians, mammals and reptiles that damage crops, livestock, poultry, and human health. Of these, nine species made up 41% of the total amount of species that were mentioned. We believe that adequate management and resolution of HWC requires the participation and training of groups of multidisciplinary scientists and technicians. Research in Mexico is scarce and recent and is mostly promoted by the conservation programs and strategies implemented by the federal government.